Inertial displacement of a domain wall excited by ultra-short circularly polarized laser pulses - Janda, T.; Roy, P.E.; Otxoa, R.M.; Soban, Z.; Ramsay, A.; Irvine, A.C.; Trojánek, F.; Surynek, M.; Campion, R.P.; Gallagher, B.L.; Němec, P.; Jungwirth, T.; et al. (Nature Publishing Group, 2017)
Domain wall motion driven by ultra-short laser pulses is a prerequisite for envisaged low-power spintronics combining storage of information in magnetoelectronic devices with high speed and long distance transmission of information encoded in circularly polarized light. Here we demonstrate the conversion of the circular polarization of incident femtosecond laser pulses into inertial displacement of a domain wall in a ferromagnetic semiconductor. In our study we combine electrical measurements and magneto-optical imaging of the domain wall displacement with micromagnetic simulations. The optical spin transfer torque acts over a picosecond recombination time of the spin polarized photo-carriers which only leads to a deformation of the internal domain wall structure. We show that subsequent depinning and micro-meter distance displacement without an applied magnetic field or any other external stimuli can only occur due to the inertia of the domain wall.